Knowledge of Pediatric Sepsis among Trainees - Qalab Abbas; Anwar ul Haque; Syed Asad Ali (Wolters Kluwer Medknow Publications, 2014)
Introduction: Sepsis is one of the leading causes of death in children inthe developing world. Several studies have shown that the knowledge and implementation of current American College of Critical Care Medicine« Pediatric Advance Life Support (ACCM-PALS) guidelines on recognition and initial management of sepsis ii children leads to significant improvement in outcomes. There is little known about the knowledge of curren guidelines on recognition and initial management of pediatric sepsis among healthcare providers in Pakistan Objectives: To assess the retention of knowledge among trainees of pediatrics after a 30 minutes didactic session on recognition and initial management of pediatric severe sepsis and septic shock. Materials and Methods: We conducted 1-hr educational session, which consisted of 30-min lecture, 20- min for assessment through 20 single best multiple choice questions and 10-min ofdebriefing for pediatric residents at seven academic institutions in Pakistan. The key components of this exercise were recognition initial five-minute management, fluid resuscitation, inotrope, antibiotics and steroid. Results: Of the 222 residents who participated, 42% (91/222) correctly answered >60% of questions with г median score of 10/20 and IQR of 18. Recognition was done correctly by 41.2% (93/222); 54% (121/222; knew about fluid resuscitation, and 27.7% (62/222) about inotropic support. Eighty % (177/222) and 70.8°À (158/222) had knowledge of steroid and antibiotic use respectively. Conclusion: The knowledge of the recognition and initial management of sepsis in children among pediatric residents is suboptimal, even after a 30 minutes didactic session on the subject.